Safety and Immunogenicity of a 4-Component Toxoid-Based Staphylococcus aureus Vaccine in Rhesus Macaques - Venkatasubramaniam, Arundhathi; Liao, Grant; Cho, Eunice; Adhikari, Rajan P.; Kort, Tom; Holtsberg, Frederick W.; Elsass, Karen E.; Kobs, Dean J.; Rudge, Thomas L.; Kauffman, Keith D.; Lora, Nickiana E.; Barber, Daniel L.; et al. (Frontiers in Immunology, 2021)
Staphylococcus aureus is a leading cause of significant morbidity and mortality and an enormous economic burden to public health worldwide. Infections caused by methicillin-resistant S. aureus (MRSA) pose a major threat as MRSA strains are becoming increasingly prevalent and multi-drug resistant. To this date, vaccines targeting surface-bound antigens have failed in clinical trials, leading us to hypothesize that targeting secreted antigens may be more efficacious. The objective of this study was to evaluate the safety and immunogenicity of a staphylococcal 4-component vaccine targeting secreted bi-component pore-forming toxins (BCPFTs) and superantigens (SAgs) in non-human primates (NHPs). The 4-component vaccine proved to be safe, even when repeated vaccinations were given at a dose that is 5 to 10- fold higher than the proposed human dose. Vaccinated rhesus macaques did not exhibit clinical signs, weight loss, or changes in hematology or serum chemistry parameters related to the administration of the vaccine. No acute, vaccine-related elevation of serum cytokine levels was observed after vaccine administration, confirming the toxoid components lacked superantigenicity. Immunized animals demonstrated high level of toxin-specific total and neutralizing antibodies towards target antigens of the 4-component vaccine as well as cross-neutralizing activity towards staphylococcal BCPFTs and SAgs that are not direct targets of the vaccine. Cross-neutralization was also observed towards the heterologous streptococcal pyogenic exotoxin B. Ex vivo stimulation of PBMCs with individual vaccine components demonstrated an overall increase in several T cell cytokines measured in supernatants. Immunophenotyping of CD4 T cells ex vivo showed an increase in Ag-specific polyfunctional CD4 T cells in response to antigen stimulation. Taken together, we demonstrate that the 4-component vaccine is well-tolerated and immunogenic in NHPs generating both humoral and cellular immune responses. Targeting secreted toxin antigens could be the next-generation vaccine approach for staphylococcal vaccines if also proven to provide efficacy in humans.